2017
DOI: 10.1039/c7sc01077j
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale metal–organic frameworks coated with poly(vinyl alcohol) for ratiometric peroxynitrite sensing through FRET

Abstract: This work describes a facile yet powerful approach to energy-transfer NMOF (nanoscale metal–organic framework) fabrication for ratiometric peroxynitrite (ONOO–) sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 47 publications
2
21
0
1
Order By: Relevance
“…It was revealed that loading molecules with strong ICT into pores of MOF or linking onto MOF surface could enhance fluorescence because of the change of the polarity of the local environment. 4143 In this nanoprobe system, as expected, efficient energy transfer from the NMOF to the molecule BPP was observed after a small amount of BPP was coated onto the surface of the NMOF. Upon reacting with ONOO – , BPP detached from NMOF and the FRET between them was destroyed, which led to the recovery of NMOF fluorescence and the fading of the BPP fluorescence.…”
Section: Resultssupporting
confidence: 80%
“…It was revealed that loading molecules with strong ICT into pores of MOF or linking onto MOF surface could enhance fluorescence because of the change of the polarity of the local environment. 4143 In this nanoprobe system, as expected, efficient energy transfer from the NMOF to the molecule BPP was observed after a small amount of BPP was coated onto the surface of the NMOF. Upon reacting with ONOO – , BPP detached from NMOF and the FRET between them was destroyed, which led to the recovery of NMOF fluorescence and the fading of the BPP fluorescence.…”
Section: Resultssupporting
confidence: 80%
“…Nanostructured probes based on different material backbones have been developed for ONOO − . Zhang and co‐workers constructed a nanoscale metal‐organic framework (NMOF), which was coated with two kinds of poly(vinyl alcohol) (PVA). A fluorophore modified with a boronic acid group was attached to the surface of the NMOF through binding to the exposed diols of PVA.…”
Section: Fluorescent Probes For the Detection Of Ros‐related Diseasesmentioning
confidence: 99%
“…An illustration of the sensing mechanism of two nanoscale metal‐organic framework based sensors, MA and MB. Reproduced with permission . Copyright 2017, The Royal Society of Chemistry.…”
Section: Fluorescent Probes For the Detection Of Ros‐related Diseasesmentioning
confidence: 99%
“…Ratiometric imaging depends on recording fluorescence intensities at two wavelengths simultaneously and calculating the ratio between the two intensities. This technique significantly reduces the effects of environmental changes around the sensor and consequently results in enhanced sensitivity [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%